El principio de seguridad y el derecho fundamental a la protección de datos personales - Falcón y Tella, Fernando (Anuario de Derechos Humanos. Nueva Época, 2009)
In this paper we study the security measures of personal files. We study article 9 of the “Ley Orgánica 15/1999, de 13 de diciembre, de Protección de Datos de Carácter Personal” and Title VIII of the “Real Decreto 1720/2007, de 21 de diciembre”, which develops a regulation on the topic. After a brief introduction we talk about two themes: first of all, the file regulations; and second, the basic, intermediate and high levels of security, examining the files included in each level and all the security measures of these files.